Analysis of Microstructure and Performance of Cr3C2/Ni60A Coating on 45 Steel for Laser Cladding Piston Rod - Jiafei Pu; Viacheslav Tarelnyk; Yao Ju; Bondarev Sergii Grigorievicth; Xingrong Wang; Qi Dong; Hongfeng Wang; Weiwei Song (Crystals)
This study investigates the preparation of a high-performance Cr3C2/Ni60A coating on 45# steel through laser cladding technology. The microstructure, residual stress, phase composition, hardness, and wear resistance of the coating are analyzed. The results reveal that the solidification structure of the molten pool exhibits a progression from coarse columnar crystals and dendrites near the interface with the substrate to equiaxial crystals at the coating surface. The coating primarily consists of Fe-Ni solid solution, Cr7C3, and Cr23C6 phases. As the Cr3C2 mass percentage in the Cr3C2/Ni60A composite powder increases, the formation of the Cr7C3 and Cr23C6 phases is suppressed. A pronounced stress concentration occurs at the interface between the coating and the substrate, leading to an increased dislocation density and localized grain deformation. When the Cr3C2 mass percentage reaches 45% and 55%, the coating surface exhibits a higher density of induced cracks due to the combined effects of microstructural changes and thermal influences. The maximum microhardness of the coating ranges from 520 HV1 to 556 HV1, approximately three times that of the substrate. The wear resistance of the coating initially increases and then decreases with increasing Cr3C2 content. The wear resistance is optimal at a 35% Cr3C2 mass ratio, with a wear loss of 0.15 mg—five times lower than that of the substrate. The primary wear mechanism is abrasive wear, although localized fatigue and adhesive wear are also observed.